A review on sunshine recorders: Evolution of operation principle and construction. (December 2021) - Wang, Yuchang; Zhang, Guoyu; Sun, Gaofei; Liu, Shi; Xu, Da; Yang, Songzhou; Wu, Linghao
Abstract: As solar power becomes more important, sunshine duration has become a critical variate for meteorological observations and research. In this review, the evolution of the operation principle and construction of sunshine recorders was summarized. Sunshine recorders were classified according to their measurement methods, and their historical and technological development were reviewed. Characters, such as thresholds, uncertainties, maintenance, and operational cost of different sunshine recorders, are compared. Then, the advantages and disadvantages of each measurement method and the sensors applied to the sunshine recorders were also discussed. At the end of the paper, we concluded that photoelectric sunshine recorder is currently the best option for sunshine duration measurement due to high-precision and low cost, and the thermoelectric sunshine recorder has the potential to dominate the sunshine duration measurement market for their wide spectral response range. The pyrheliometric and pyranometric methods are the mainstream for designing recorders in the future period.